Design thinking in traffic safety education for high school students in Ho Chi Minh City - Trịnh Tú Anh; Phạm Nguyễn Hoài; Lê Phúc Toàn; Lê Phan Trường An; Lê Quốc Việt; Trịnh Thùy Anh (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Khoa học Xã hội, 2023)
Enhancing knowledge and skills in traffic safety through education is the goal of many countries. In addition, virtual reality technology has the potential to create an interactive, effective, and safe learning environment for learners. Therefore, this study applies the design thinking method, including five important steps (empathize, define, ideate, prototype, and test), to construct a virtual reality traffic environment, providing high school students in Ho Chi Minh City with a realistic experience related to this field. Focus group discussions were conducted with 32 students to investigate factors including immersion, presence, and interaction in the virtual reality traffic environment. The results showed that the students immersed themselves in the virtual traffic environment, felt their presence, and interacted with elements in the environment. Further in-depth research on virtual reality traffic environments is needed in the future to ensure feasibility in implementation and establish a foundation for traffic safety education for high school students in Ho Chi Minh City.